Hieratic Harmonies: An Analysis of Tonal Conflict in Stravinsky's Mass - Annicchiarico, Joseph. (2017)
Abstract: Igor Stravinsky's Mass is the penultimate work of his neoclassical phase, written between the years of 1944 and 1948, just before his landmark piece The Rake's Progress. The Mass is a highly "conflicted" work, both culturally and musically. As World War II was racing towards its tumultuous end, Stravinsky—oddly, without commission—decided to write a Mass, which is peculiar for someone who converted to the Russian Orthodoxy many years earlier. Musically speaking, the work exhibits conflicts, predominantly in the dialectic between tonality and atonality. Like the war, Stravinsky himself was nearing a turning point—the end of his neoclassical style of composition—and he was already thinking ahead to his opera and beyond. This thesis offers an analysis based on the idea of musical conflict, highlighting the syntactical dialogues between two tonal idioms. My work focuses heavily in particular on the pitch-class set (4-23) [0257], and the role that it plays in both local and global parameters of the work, as well as its interactions with non-functional tonal elements. Each movement will be analyzed as its own unit, but some large-scale relations will be drawn as well. My analysis will bring in previous work from two crucial investigations of the work—by V. Kofi Agawu, and by the composer Juliana Trivers. The Mass has never been a widely discussed work in the oeuvre of such a popular composer, but my hope is that this thesis can help rectify this by bringing overdue analytical attention to crucial elements of Stravinsky's language in the piece.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Music.; Advisor: Frank Lehman.; Committee: Joseph Auner, and Janet Schmalfeldt.; Keyword: Music.